Listening comprehension challenges and facilitating factors among Indonesian EFL students in English-speaking countries : A Phenomenological study - Laksmy Ady Kusumoriny; Abdul Aziz (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Listening plays a crucial role in individuals’ communication with others and in their efforts to comprehend their surroundings. As one of the fundamental tools for learning, it serves as a foundation for the development of other language skills and is frequently employed both in everyday life and within educational contexts. Consequently, listening emerges as a key component in foreign language instruction. Learners’ ability to comprehend what they hear is essential to avoid difficulties in the language learning process. In the context of teaching English as a foreign language, the careful monitoring of learners’ listening processes and the identification of the challenges they face are vital for achieving instructional success. This study aims to identify the listening-related difficulties encountered by university students learning English as a foreign language at the Intermediate proficiency level. Grounded in a qualitative research approach, the study adopts a phenomenological design. The participants consisted of eight Indonesian students enrolled in English speaking countries such as US, Canada, Australia and UK. Data were collected through semi-structured interviews conducted with the selected participants. A descriptive analysis technique was employed to analyze the qualitative data. The participants reported several common difficulties during listening activities, including heavily accented speech, frequent use of idioms and proverbs, limited vocabulary knowledge, lack of attention to stress and intonation, and the speaker’s rapid speech rate. On the other hand, several facilitating factors were also identified. These included prior knowledge of other languages, having a rich vocabulary, engaging and interesting content, the presence of audiovisual elements, and the effective use of gestures and facial expressions by the speaker—all of which contributed to improved listening comprehension.